Boron Nanosheet-Supported Rh Catalysts for Hydrogen Evolution: A New Territory for the Strong Metal-Support Interaction Effect - Chen, Keng; Wang, Zeming; Wang, Liang; Wu, Xiuzhen; Hu, Bingjie; Liu, Zheng; Wu, Minghong (Nano-Micro Letters, 2021)
High-efficiency electrochemical hydrogen evolution reaction (HER) offers a promising strategy to address energy and environmental crisis. Platinum is the most effective electrocatalyst for the HER. However, challenging scarcity, valuableness, and poor electrochemical stability still hinder its wide application. Here, we designed an outstanding HER electrocatalyst, highly dispersed rhodium (Rh) nanoparticles with an average diameter of only 3 nm supported on boron (B) nanosheets. The HER catalytic activity is even comparable to that of commercial platinum catalysts, with an overpotential of only 66 mV in 0.5 M H2SO4 and 101 mV in 1 M KOH to reach the current density of 10 mA cm−2. Meanwhile, the catalyst exhibited impressive electrochemical durability during long-term electrochemical processes in acidic and alkaline media, even the simulated seawater environment. Theoretical calculations unraveled that the structure–activity relationship between B(104) crystal plane and Rh(111) crystal plane is beneficial to the release of hydrogen, and surface O plays a vital role in the catalysis process. Our work may gain insights into the development of supported metal catalysts with robust catalytic performance through precise engineering of the strong metal-supported interaction effect. Highlights: 1 Ultra-small and highly dispersed rhodium nanoparticles anchored in 2D ultra-thin boron nanosheets (BNS) were synthesized by a rapid NaBH4 reduction and facile freeze-dry approach. 2 Due to the strong metal-support interaction effect, the optimized electrocatalyst exhibits excellent hydrogen evolution reaction (HER) catalytic activity and stability in the wide pH range electrolytes. 3 Based on the stable surface, the oxidized boron surface facilitates the coupling of BNS and metal, giving catalyst outstanding HER performance.